Literary Text in the Spanish as a Foreign Language Class: Proposals and Use Models - Jouini, Khemais (Íkala, Revista de Lenguaje y Cultura, 2008)
This article aims to propose the introduction of the literary text to the programs of Spanish as a foreign language (S/FL). The literary text in this frame is meant to be a communication act and a means for teaching / learning Spanish as a foreign language within an institutionalized and artificial context made suitable for an intermediate / advanced student profile. The research gives considerable importance to the literary text as an input that catalyzes a variety of both oral and written activities and as a didactical means integrating communication skills. Moreover, it establishes some selection criteria in order to target the characteristics of the texts to be used, in accordance with linguistic goals, contents and students' needs and interests, suggesting some useful didactical and methodological parameters for enhancing suitable activities for all text types. Finally, two practical proposals for transforming a literary text into a communication activity are presented. Received: 26-02-2008/ Accepted: 10-08-2008 How to reference this article: Jouini, K. (2008). El texto literario en la clase de español como lengua extranjera: propuestas y modelos de uso. Íkala. 13(2), pp.121-159.